2020
DOI: 10.4103/ija.ija_975_19
|View full text |Cite
|
Sign up to set email alerts
|

Total intravenous anaesthesia with tumescent infiltration anaesthesia without definitive airway for early excision and skin grafting in a major burn - A prospective observational study

Abstract: Background and Aims: Patients with major burns posted for early tangential excision and skin grafting pose peculiar challenges for anaesthesiologists. The purpose of the study was to assess safety and efficacy of total intravenous anaesthesia (TIVA) with tumescent infiltration anaesthesia (TIA) for these burn procedures. Methods: This observational single-arm study was conducted on 48 cases of a tertiary centre burn unit, requiring early tangential excision and skin gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Salgaonkar et al, in their study, had administered TIVA with tumescent infiltration anesthesia (TIA) and found that 95.8% of the patients had achieved an Aldrete score of 9 or more at 10 min post-surgery. 5 The prevalence of moderate and severe pain was significantly higher in Group G compared to Group T, whereas the prevalence of mild pain was significantly higher in Group T compared to Group G. Pain management was better in Group T patients compared to Group G patients.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Salgaonkar et al, in their study, had administered TIVA with tumescent infiltration anesthesia (TIA) and found that 95.8% of the patients had achieved an Aldrete score of 9 or more at 10 min post-surgery. 5 The prevalence of moderate and severe pain was significantly higher in Group G compared to Group T, whereas the prevalence of mild pain was significantly higher in Group T compared to Group G. Pain management was better in Group T patients compared to Group G patients.…”
Section: Discussionmentioning
confidence: 76%
“…4 The primary goal of management is to stabilize the patient and provide biological cover for the wounds. 5 Kisslagglu et al, revealed that early excision and skin grafting procedures resulted in reduced hospitalization duration and lower costs of burn treatment compared to conservative management. 6 These procedures aim to minimize the risk of infection and scarring while improving cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The epinephrine in the mixture causes vasoconstriction, which is further enhanced by the tamponading effect of the high volume infiltration on the subdermal vessels (7). Another potential advantage is the analgesic effect offered by the local anesthetic which has been confirmed by researchers (8,9).…”
Section: Introductionmentioning
confidence: 90%
“…[10][11][12] Numerous studies have been conducted on the effect of analgesic and sedative agents such as ketamine, fentanyl, propofol, and midazolam for pain reduction during dressing change in patients with burns. 13,14 Despite the administration of high dosages of analgesics, patients still experience intense pain during these treatments. 15 In addition, the harmful complications of these medications in high doses can aggravate patients' condition.…”
Section: Introductionmentioning
confidence: 99%